1992
DOI: 10.1111/j.1471-4159.1992.tb08338.x
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyphenylalanine and Dopamine Are Released from Portal Vein Together with Noradrenaline and Dihydroxyphenylglycol During Nerve Stimulation

Abstract: The overflows of 3,4-dihydroxyphenylalanine, dopamine, noradrenaline, and 3,4-dihydroxyphenylglycol in canine portal vein superfused in vitro were studied before, during, and after depolarization of sympathetic nerve endings. The four compounds were separated from superfusate and from tissue on Sep-Pak C-18 cartridges and quantified by HPLC with electrochemical detection. Physiological and biochemical methods were used to show that the compound released was most probably 3,4-dihydroxyphenylalanine; the identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Tyrosine hydroxylase is principally confined to catecholamine-producing tissues [ 13. A number of findings do not, however, support this theory: ( I ) There is no depot of DOPA in sympathetic nerves or alternatively it is very small as compared to amounts of DOPA in muscles [3]; (2) There is clearly no close relationship between sympathetic activity as determined by plasma norepinephrine and plasma DOPA [2, 4, 5, 61; (3) In vitro studies have demonstrated a very small DOPA overflow as compared to the norepinephrine overflow whereas DOPA concentrations in plasma are much higher than those of norepinephrine [7]. Some authors have concluded, that plasma DOPA levels appear to reflect the rate of tyrosine hydroxylation throughout the body, including to some extent brain (for review see [2]).…”
Section: 4-dihydroxyphenylalaninementioning
confidence: 99%
“…Tyrosine hydroxylase is principally confined to catecholamine-producing tissues [ 13. A number of findings do not, however, support this theory: ( I ) There is no depot of DOPA in sympathetic nerves or alternatively it is very small as compared to amounts of DOPA in muscles [3]; (2) There is clearly no close relationship between sympathetic activity as determined by plasma norepinephrine and plasma DOPA [2, 4, 5, 61; (3) In vitro studies have demonstrated a very small DOPA overflow as compared to the norepinephrine overflow whereas DOPA concentrations in plasma are much higher than those of norepinephrine [7]. Some authors have concluded, that plasma DOPA levels appear to reflect the rate of tyrosine hydroxylation throughout the body, including to some extent brain (for review see [2]).…”
Section: 4-dihydroxyphenylalaninementioning
confidence: 99%
“…J. Neurochem. 64,833-841 (1995) .3,4-Dihydroxyphenylanine (DOPA) overflows from isolated superfused segments of canine portal vein together with norepinephrine (NE) and 3,4-dihydroxyphenylglycol (DHPG) (Hunter et al, 1992) . The overflow of DOPA is increased in a frequency-dependent manner by nerve stimulation .…”
mentioning
confidence: 99%
“…DOPA is a pivotal com-833 pound in the synthesis of NE because it is the product of tyrosine hydroxylation, the rate-limiting reaction in catecholamine synthesis (Levitt et al ., 1965) . In the portal vein we showed that when tyrosine hydroxylase (TH) was inhibited, DOPA efflux was greatly attenuated (Hunter et al ., 1992), and when TH activity was increased as a result of nerve stimulation (Alousi and Weiner, 1966), DOPA efflux was increased . Thus, we proposed that quantification of DOPA in superfusates could be useful as an index of TH activity (Hunter et al ., 1992) .In the present study we initially measured the effluxes of DOPA, NE, and DHPG from four different isolated blood vessels of the dog : saphenous and portal veins and pulmonary and mesenteric arteries .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was correlated with the change in blood pressure during the dark-active phase monitored by the tail cuff method ( Figure 7F). Because L-DOPA is an endogenous ligand for GPR143 and is released from sympathetic neurons and adrenal medullae in an activity-dependent manner (3)(4)(5)33), it is possible that the disruption in day and night blood pressure variation in Gpr143 -/y mice might be due to dysfunction of the sympathetic nervous system. To examine possible involvement of sympathetic activity, we measured plasma levels of L-DOPA, noradrenaline (NA), and adrenaline (Ad) in these mice during light and dark phases.…”
Section: E-l) No Differences Between Wt and Gpr143mentioning
confidence: 99%